Sustainable tourism model in the new normal era - Sunardi, Sunardi; Roedjinandari, Nanny; Estikowati, Estikowati (Linguistics and Culture Review, 2021)
The Bromo TenggerSemeru area is a strategic area for national and world tours with natural and cultural potential. Sustainable tourism management is needed so that it area becomes a destination that has been beneficial to the community for a long time to make the area a sustainable tourist attraction; stakeholders and local communities need to be prepared. This study aims to examine the sustainable tourism management model with qualitative and quantitative research methods with descriptive analysis to identify and explore the socio-cultural aspects of society, the environment, economic growth, tourist satisfaction, and community welfare. This study resulted in findings in the form of a sustainable tourism management model in the new normal era as the primary goal of the National Tourism Development pattern based on natural and cultural beauty with the central pillars being environmental conservation, cultural preservation, tourist satisfaction, a healthy economy, and community welfare. Tourism must be able to coexist with other sectors to minimize the impact of the inherent vulnerability in tourism, tourism stakeholders need to change the tourist target market and type of tourism in order to adapt to the (post) pandemic situation.